2015
DOI: 10.2147/dddt.s83514
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and evaluation of anticancer efficacy of stigmasterol in a mouse model of DMBA-induced skin carcinoma

Abstract: Stigmasterol (99.9% pure) was isolated from Azadirachta indica and its chemopreventive effect on 7,12-dimethylbenz[a]anthracene (DMBA)-induced skin cancer was investigated in Swiss albino mice. Skin tumors were induced by topical application of DMBA and promoted by croton oil. To assess the chemopreventive potential of stigmasterol, it was orally administered at a concentration of 200 mg/kg and 400 mg/kg three times weekly for 16 weeks. Reduction in tumor size and cumulative number of papillomas were seen as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 12 publications
1
59
0
1
Order By: Relevance
“…It has been demonstrated that sitosterol acts as an inhibitor of tumor promotion in vivo and that it inhibits carcinogenesis (7,8). Furthermore, stigmasterol significantly inhibits tumor promotion in two-stage carcinogenesis in mice (7,9). A mixture of sitosterol and stigmasterol was indicated to possess anti-inflammatory activity following topical application (10).…”
Section: Phytochemical Analysis Of G Tournefortii Using Gc-msmentioning
confidence: 99%
“…It has been demonstrated that sitosterol acts as an inhibitor of tumor promotion in vivo and that it inhibits carcinogenesis (7,8). Furthermore, stigmasterol significantly inhibits tumor promotion in two-stage carcinogenesis in mice (7,9). A mixture of sitosterol and stigmasterol was indicated to possess anti-inflammatory activity following topical application (10).…”
Section: Phytochemical Analysis Of G Tournefortii Using Gc-msmentioning
confidence: 99%
“…5 However, in this study, sterols were found to be the major constituents of the HEX, DCM, and EA extracts from A. donax L. with 52%, 42%, and 30% relative content, respectively. Although sterol was found in methanolic 11 anticancer effects against skin carcinoma, 12 and antidiabetic activities. 13 Thus, A. donax L. rhizome maybe one important source of sterol compounds for further medicinal application.…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer activity has been observed in the species of Cyperus rotundus [30,31]. It is reported that stigmasterol also has anticancer activity in a mouse model of 7,12-dimethylbenz(a)anthracene-induced skin carcinoma [32]. Therefore, it can be suggested that various works associated with free radical generation in the body such as anticancer activity could be performed on the different extracts of Cyperus tegetum.…”
Section: Discussionmentioning
confidence: 99%